Implementation of a Centralized Cloud-Based Hotspot Voucher Management System and Network Traffic Monitoring Using MikroTik Virtual - Cristovani Ari Wibowo Lohonauman; Christopel Hamonangan Simanjuntak; Maksy Sendiang; Herry Setiawan Langi; Venny Vita Ponggawa (Tecno Scientifica Publishing, 2026)
Hotspot voucher services became one of the most widely adopted solutions among local Internet Service Providers (ISPs) because they facilitated user access control, usage duration management, and bandwidth allocation. In the existing network environment, hotspot voucher sales were operated at two different locations. However, the management of these locations was still performed independently using separate MikroTik routers. This condition created several challenges, including decentralized voucher data, standalone user authentication processes, inefficient voucher administration, and the inability to perform comprehensive network traffic monitoring. This study implemented a centralized hotspot voucher management system using a MikroTik Cloud Hosted Router (CHR) to integrate two hotspot voucher sales locations into a unified management platform. The MikroTik CHR was deployed in a cloud computing environment and functioned as the central server for voucher management, user authentication, and network traffic monitoring. Each MikroTik router at the voucher sales locations was connected to the MikroTik CHR through a VPN tunnel. Furthermore, a web-based application was developed as a management interface and was integrated with the MikroTik CHR through an Application Programming Interface (API). The application enabled administrators to generate vouchers, monitor voucher status, manage users, and observe network traffic through a centralized dashboard. The research adopted the Network Development Life Cycle (NDLC) methodology, which consisted of the stages of analysis, design, simulation, implementation, monitoring, and management. The implementation results demonstrated that the centralized system successfully integrated voucher management across two different locations, simplified administrative processes, supported centralized user authentication, and provided unified network traffic monitoring through a single platform. Therefore, the implementation of MikroTik CHR in a centralized hotspot voucher system improved management efficiency and supported the expansion and sustainability of hotspot services across multiple locations.